Enhancer of zeste 2 polycomb repressive complex 2 subunit promotes sorafenib resistance of hepatocellular carcinoma though insulin-like growth factor 1 receptor. Issue 7 (August 2019) - Hu, Jing; Zhang, Jing; Sun, Feifei; Qi, Mei; Su, Peng; Liu, Hui; Gao, Lin; Jiao, Meng; Wu, Zhen; Xiang, Lei; Han, Bo
Abstract : Enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) is the core component of polycomb repressive complex 2 and is overexpressed in several types of solid malignancies. It has been reported that EZH2 contributes to sorafenib resistance of hepatocellular carcinoma (HCC). However, its underlying molecular mechanisms remain unknown. In this study, we demonstrated that EZH2 induced sorafenib resistance of HCC cells in vitro . Mechanistically, EZH2 was a potent regulator of insulin-like growth factor 1 receptor (IGF1R) and EZH2-modulated IGF1R expression by directly transcriptionally repressing a set of microRNAs (miRNAs) including miR-101, miR-122, miR-125b, and miR-139. These miRNAs were required for EZH2-mediated sorafenib resistance by promoting IGF1R expression. Surprisingly, IGF1R inhibitors significantly reversed EZH2-induced sorafenib resistance. Collectively, we proposed a novel model for an EZH2 – miRNAs – IGF1R regulatory axis, which might provide insights into how EZH2 contributes to sorafenib resistance in HCC. Abstract : Supplemental Digital Content is available in the text.